(untitled) (Global Journal of Science Frontier Research, 2012)
The use of mathematics in everyday life often goes unnoticed by the person who exploits mathematics and also by the person who associates with the person who exploits mathematics. This article looks at mathematics as a discipline and it serves to inform people, in general, about the importance of mathematics in the world we live in and how in many ways, human beings have contributed to its sophistication in the application and working worlds.